Gerenciamento de tensões organizacionais e geração de valor social nos negócios de imapcto - Lima, Diego Sampaio Vasconcelos Ramalho (2024)
Impact businesses have been gaining prominence in the academic and managerial spheres as they seek to reconcile socio-environmental objectives with financial sustainability. This hybrid organizational format, which operates according to market logic and has a concern with impact at the center of its operations, is composed of organizational tensions. These organizational tensions are categorized into eight dimensions: organizational objective, legality, organizational evolution, financial resources, profits, human resources, interorganizational relations and entrepreneurial process. Knowing that the ultimate objective of impact businesses is the generation of social value, and that managing organizational tensions is fundamental to organizational continuity and success, this work sought to fill a gap in research on tensions and social value. Therefore, the objective of this research was to understand how the management of organizational tensions affects the generation of social value in impact businesses. Taking the impact ecosystem of the State of Ceará as a context, a qualitative research approach was carried out, through multiple case studies, with six impact businesses in Ceará. The following sources of evidence stand out: carrying out 21 semi-structured interviews with entrepreneurs and other actors in the ecosystem; preparation of 13 direct observation reports; and document and social media analysis. The data was analyzed using content analysis. The results showed that managing organizational tensions increases the generation of social value in impact businesses. Some management actions used by businesses were: expanding business partnerships; analyze the complete business value chain; carry out effective communication of the social purpose of the business; measure the value and impacts generated; develop strategic growth plans for each sector of the company. The management of organizational tensions in their various dimensions interconnects and permeates the specific issues of tension and the expansion of the generation of social value occurs through the increase in productive capital, human capital, social capital, physical capital, natural capital, reuse of material and of citizenship.